(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Aggression is a behavioral characteristic that refers to forceful actions or procedures (such a deliberate attack) with intentions to dominate or master. It tends to be hostile, injurious, or destructive, and is often motivated by frustration for an individual, aggressive behavior is considered understandable and normal under appropriate circumstances, but when it is frequent, intense, lasting, and pervasive, it is more likely to be a symptom of a mental disorder. Likewise, aggression between groups, can be in the form of healthy competition, but can become harmful when unfair or unjust disadvantage or frustration is perceived, leading to hostility. Objectives: assessment aggression among high school students. Methodology: A descriptive cross-sectional study was carried out in order to achieve the stated objectives. The study has begun from 1st September 2018. Settings of the Study: The settings of the study include (41) High secondary schools which are distributed in (3) Districts of Al-Najaf Governorate, urban (23) schools and rural (18) schools, these schools are systematic randomly selected. Results: most majority was moderate aggressive by 52.7%. Conclusions: this study show which included an overall assessment of Aggressive, where the study showed that the most majority was moderate aggressive. Recommendations: Supporting educational methods by the Educational Committee that limits aggressive behavior of adolescents in schools, such as (moving away from scenes of an aggressive nature, beating, violence, fighting, quarrels, and blood scenes). And The teacher devotes part of the lesson time to clarifying issues and harms of aggression, and to show the benefits of tolerance and contentment. and The school administration cooperated with the teenager’s family to identify the causes of his aggression. Finally, The Ministry of Education is working to create posters that reject aggression and suspend it throughout the school.